Visual Identity Design in Events: A Strategic Approach to Improve Image and Attractiveness at the Bandung Shocking Sale Festival Event - Rinaldi, Mario; Satyadharma, I Gede Nyoman Wisnu (Indonesian Journal of Advanced Research, 2025)
Visual identity is one of the essential aspects of a branding strategy, which includes elements such as logos, color palettes, typography, and other design elements that shape the public's perception of a product or event. This design aims to explore the role of visual identity in improving the image as well as being the main attraction of an activity. In the context of the Bandung Shocking Sale Festival, the design of the right visual identity is expected to be able to attract more visitors while strengthening the position and identity of the event in the city of Bandung. As the number of similar events increases, a clear differentiation effort is needed so that the Bandung Shocking Sale Festival can compete and have a unique value in the eyes of the public. This study uses a descriptive qualitative method with data collection techniques in the form of interviews, observations, and documentation, and is complemented by literature studies and tracing of other literature sources to obtain secondary data. The final design results are in the form of soft logo files, logo design derivatives, and the application of visual identity in various promotional media that are relevant to the needs of the event.